The Influence of Competence and Work Experience on The performance of The People's Economy Bank With Democratic Leadership as an Intervening Variable - Yudiarsa, I Nyoman; Yuniningsih; Swasti , Ika Korika (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the influence of leadership and work motivation on lecturer performance, both directly and indirectly through job satisfaction as a mediating variable at Nazhatut Thullab Al-Muafa University, Sampang. This study used a quantitative approach with the SEM-PLS method. The study population was all 66 permanent and non-permanent lecturers, using a census method (total sampling). The primary theory underlying this study is Goal Setting Theory. This study used a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results show that leadership can contribute to lecturer performance. Work motivation contributes to lecturer performance. Leadership contributes to lecturer performance through job satisfaction. Similarly, motivation contributes to lecturer performance through job satisfaction. These findings theoretically sharpen and expand the concepts discussed, and practically can serve as guidelines for Nazhatut Thullab Al-Muafa University, Sampang, in improving lecturer performance, evaluating, and driving institutional progress. Kata Kunci: Leadership, Work Motivation, Job Satisfaction, Lecturer Performance